Leukocyte adhesion proteins: their role in neutrophil function. - Root, R. K. (American Clinical and Climatological Association, 1990)
In conclusion, the leukocyte proteins of the CD11/18 complex are highly conserved members of the integrin family in mammalian species. They play a key role in phagocytic and adherence mediated activities of neutrophils and appear to be centrally involved in adhesion to endothelial cells as well as transendothelial migration. Their importance in these processes has been documented by the occurrence of the disease now called leukocyte adhesion deficiency and the functional effects of a variety of monoclonal antibodies directed at different epitopes on the heterodimeric glycoprotein chains. These antibodies, as well as those directed at endothelial cell ligands for leukocyte adhesion proteins or peptides which mimic the functional epitopes, offer opportunities to manipulate or modify the inflammatory response in vivo where neutrophil accumulation or action can be harmful. They can also be employed to dissect out the role of PMNs in various repair processes such as wound healing. While bone marrow transplantation can ameliorate the deleterious consequences of severe LAD, continued elucidation of the multiple molecular mechanisms responsible for this disease will pave the way for its future genetic correction.